Cellulose Supported Poly(amidoxime) Copper Complex for Click Reaction - Sarkar, Shaheen M.; Lutfor, M. R. (Elsevier Ltd, 2017)
A highly active poly(amidoxime) copper complex was prepared by the surface modification of kenaf cellulose through graft copolymerization and subsequent amidoximation. The prepared copper complex was characterized by IR, FESEM, TEM, XPS, EDX and ICP-AES analyses. The copper complex was applied to the Click reaction of organic azides and alkynes as well as one-pot three-component reactions in presence of sodium ascorbate to give the corresponding cycloaddition products in up to 96% yield. The complex was easy to recover and reused six times without significance loss of its activity.